Effect of Formulation Variables on Phenobarbital Release from HPMC Matrices: Phenobarbital release from HPMC matrices - Maryam Maghsoodi,; Ali Nokhodchi,; Leila Barghi, (Iranian Journal of Pharmaceutical Sciences, 2008)
Controlled release swellable tablets of phenobarbital were prepared by a simple direct compression process using hydroxypropyl methylcellulose (HPMC) as the matrix former. The effects of the viscosity grades of HPMC and HPMC/lactose ratio and ethylcellulose (EC)/sodium carboxymethylcellulose (NaCMC) and their concentrations on the release behavior of phenobarbital from HPMC matrices were investigated. In order to determine the mode of release, the data were analyzed based on the equation Q= K tn. Higher drug release rate was found for formulations with lower HPMC/lactose ratios and lower HPMC viscosity grades. The viscosity of HPMC polymer has a large influence on the erosion rate of matrix tablet. Use oflow viscosity grade of HPMC polymer is desired for drugs that are poorly water soluble such as phenobarbital since the erosion rate of tablet matrix is the controlling factor for drug release. As the proportion of EC or NaCMC in admixture with HPMC increased, the release rates gradually increased. It is also observed that the amount of HPMC played a dominant role, affecting the drug release in binary mixtures.Invitrorelease studies demonstrated that use of an appropriate blend of HPMC and EC or NaCMC enables to better control of drug release profiles and approach to zero order kinetic.